Urolithiasis and pyelonephritis in Macaca fascicularis - a case report - Omar, Abdul Rahman; Noor, Faridah (Malaysian Society of Applied Biology, 1981)
A case of recurrent bilaterial pyelonephritis in an adult male Macaca fascicularis is reported. The condition was probably initiated by a cystic calculus. The animal died from acute renal failure during an acute terminal episode.